How do parents of children with ASD use information grounds to seek for ASD‐related information?. Issue 1 (18th October 2019) - An, Jiaxin; Na, Ying; Zhang, Pengyi
ABSTRACT: Parents of children with an autism spectrum disorder (ASD) have special needs about health information related to children. This research aims to understand how parents of children with ASD in China seek information in information grounds. We conducted field observations at a treatment and rehabilitation center, and interviewed 16 Chinese parents of children with ASD whose children participated in the therapy classes at this center. Results derived from qualitative coding and analysis suggest that: (1) parents' information needs evolve around improving their children's living skills, social connections are important information sources for them. (2) Parents' information grounds are closely related to their everyday life of looking after the children, such as classes and activities. Main topics of information sharing and exchange at such places include experiences of raising children with special needs, children's health status, and other child‐bearing topics. (3) Factors influencing parents' information behavior in the information grounds include homogeneity, familiarity, focal activity, reward expectation, and so on. (4) Parents benefit from such information grounds to gain useful information, emotional support, and social connections. These findings provide insights on better understanding the unique needs of parents with ASD children.